Empowering Leadership dalam Peningkatan Kreativitas Karyawan - Santi Retno Sari; Kumba Digdowiseiso (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2022)
The purpose of this study is to examine empowerment leadership and its dimensions and include creative self-efficacy variables in influencing employee creativity. The study took a population of employees at three companies, the sample measurement using the Slovin formula to get 159 employees was taken using a simple random sampling technique. The results show that the increase in the practice of empowering leadership and creative self-efficacy of employees will increase employee creativity. Five dimensions of empowerment leadership, only the leading by example dimension has been shown to affect employee creativity. Companies are expected to apply leadership that empowers employees and create programs to increase employee creative self-efficacy in an effort to increase employee creativity.